The Samaria Ivories, Marzeaḥ and Biblical Texts - Beach, Eleanor Ferris (The Biblical archaeologist, 1992)
Among the best known Iron Age remains from Israelite territory are the ivory carvings excavated from Samaria. These carvings have been described as the symbolic backdrop for the marzeaḥ, an association for periodic religious celebrations that is mentioned several times in the Bible. These carvings have never been used as iconographic resources for interpreting the marzeaḥ or for explaining biblical passages that might have been influenced by them, however. Some of Samaria's badly damaged examples may have been meaningful religious symbols and not just decorations.